Atravessando fronteiras: vulnerabilidade, relações de consumo e bem-estar de refugiados sob a ótica do macromarketing - Dantas, Bruna Lourena de Lima (2021)
Forced migration and the arrival of refugees in several parts of Brazil imply the need to understand the issue on refuge and systemic adjustments by institutions and society. This context leads to the theory that consumer well-being can mitigate the effects of vulnerabilities experienced by refugees in the migration process. In order for this proposition to be developed, three guiding questions have been asked: What are the main vulnerabilities and challenges faced by Venezuelan refugees in the city of João Pessoa, Brazil? How can consumption contribute to minimize refugees’ vulnerabilities and promote their well-being? What are the attributions of organizations and society concerning welcoming and integrating refugees? In order to analyze how the macromarketing actions promoted by organizations and society enable the access to consumption and, consequently, the well-being of Venezuelan refugees residing in the city of João Pessoa, Brazil, as well as to analyze the questions and the objective, a qualitative approach was adopted to investigate three actors who are Venezuelan refugees residing in such city, NGO and CSO associates who take part in mediating the refugees’ process of integration, and entrepreneurs who have employed refugees in the city. Thus, the oral story technique was adopted for the refugees along with semi-structured interviews with mediators and entrepreneurs. There was also non-participant observation in NGOs and in the meetings of the institutions with public power in order to discuss the cause on refuge. This way, data were analyzed through content analysis with the Atlas.ti software. It was possible to see that the main vulnerabilities of Venezuelan refugees are poverty, hunger, lack of medication and political persecution in Brazil, besides the difficulty to communicate, to have their documents issued, begging, xenophobia, sexual harassment, and social exploitation. Concerning their well-being, and based on eudaimonic, hedonic and social perspectives, it was possible to see that through integration, access to housing, food and consumption of goods autonomously, migrants find joy in their lives, and factors such as concern about their relatives who are in Venezuela may be an obstacle to achieving their well-being. Concerning organizations and companies, these research findings noticed an important role of the catholic and evangelical churches, as well as Christian ethics as a boosting element to welcome the refugees, as practiced by the residents of the state of Paraíba. Despite the solidarity that is so present in the residents of the Northeastern region of Brazil, there is room for awareness and sensitization of society concerning refugees’ rights and customs as well as the need to expand the welcoming of several profiles of refugees by NGOs. This way, it is believed that the theory has been confirmed, for, concerning theoretical and practical implications, the results achieved through this research help to understand the refugees’ vulnerability, to clarify the concept of well-being and to find strategies to promote it through integration and consumption by giving insights so that organizations and society may work systematically with macromarketing actions.